Discourse Practice of Nationalism in Anies Baswedan’s Sermon at the UII Campus Mosque: A Meso Dimensional Analysis of Norman Fairclough - Syah Jihan Akbar Pasya; Nani Darmayanti; Fahmy Lukman (GoAcademica Research & Publishing, 2026)
This study aims to analyze the discourse practice of nationalism in Anies Rasyid Baswedan’s sermon at the Ulil Albab Mosque of Univeritas Islam Indonesia (UII) during Ramadan 2025 using Norman Fairclough’s Critical Discourse Analysis approach at the meso dimension or discourse practice level. The study focuses on the processes of production, distribution, and consumption of discourse as discursive practices that construct nationalism within academic and religious public spaces. The research data consist of sermon transcripts, video documentation, event context, and audience responses analyzed qualitatively through descriptive methods. The findings reveal that Anies Baswedan’s sermon was produced through his identity as an intellectual-political figure who utilized the campus mosque as a space of moral and intellectual legitimacy. The discourse was distributed through digital media platforms such as YouTube, Instagram, TikTok, and online media, expanding the reach of nationalist ideas to broader audiences, particularly young generation and academics. The consumption of discourse indicates that student audiences perceived the sermon not merely as a religious lecture, but also as a socio-political reflection on education, democracy, and Indonesia future issue. Therefore, the discourse practice in Anies Baswedan’s sermon constructs an inclusive form of nationalism centered on education, social justice, and youth participation.